Tingkat Kepuasan Konsumen Terhadap Kualitas dan Harga Daging Sapi Yang Dijual di Kota Banda Aceh - Ratnawati Ratnawati; Nurliana Nurliana; Razali Razali (Jurnal Agripet, 2014)
(The level satisfaction of consumers to quality and price of beef in Banda Aceh)ABSTRACT. This study aims to determine level satisfaction of consumers to quality and price to beef sold in Banda Aceh, knowing influence of quality and beef price to satisfaction of consumer and also know most dominant variable have an effect on to satisfaction of beef consumer in Banda Aceh. The sampling methods is that used was purposive sampling is counted 180 consumers. The level of beef consumer satisfaction to sold in Banda Aceh is in the level of very low. The quality and price to the satisfaction of consumers to beef sold in Banda Aceh has significant different to satisfaction of consumers P0,05. The quality variable which significantly has a dominant of beef consumer satisfaction to sold in Banda Aceh. The value of determination coefficient (R Square) is equal to 0,31,9 show that quality and price of beef is influenced satisfaction of consumers is equal to 31,9 %, meanwhile 68,1% is influenced by other factors not included in this study. Concluded that the quality and price have ability to influence satisfaction of consumers. The good quality can improve satisfaction of consumers and stiff price can degrade satisfaction of consumers.